Stimulus Gambar: Sebuah Kajian pada Instrumen Minat Vokasional - Firmanto Adi Nurcahyo; Saifuddin Azwar; Wisjnu Martani (Buletin Psikologi, 2018)
Vocational interest instruments are mostly based on verbal stimuli which require subjects’ reading ability. Another form of stimuli is needed for the populations that have reading difficulty. This article offers an explanation of using pictures as stimuli in the development of an instrument to assess adolescents’ vocational interest as well as the steps in developing pictorial stimuli. Compared to verbal, pictorial stimuli are closer to real life and have supporting information related to the activities. However, some limitation in using pictorial stimuli such as difficulty in describing hardly observable behavior and ambiguity of the pictures that can affect individual interpretation need to be considered.